Pengelolaan Sarana Pendidikan di Sekolah Menengah Kejuruan Negeri di Kota Padang - M.Hafyzh Caniago; Anisah Anisah; Ermita Ermita (Universitas Negeri Padang, 2020)
The purpose of writing articles to obtain information about Management of Education Facilities at Vocational High School in the City of Padang. The population in this study is the manager of educational facilities at State Vocational High School In Padang City amounting to 40 people. The data collection technique is done by spreading the questionnaire to all populasidenga using the mean formula. The results showed that the management of educational facilities at Vocational High School in the City of Padang, with details of the research results as follows, the planning of education facilities has been done well (76%), procurement of educational facilities have been done well (77.7%), (74.1%), the utilization of educational facilities has been well implemented (80.6%), maintenance of educational facilities have been done well (74.6%) and the elimination of pedidika facilities has been done quite well ( 64.2%). From the description of research results can be concluded that the overall management of educational facilities at Vocational High School in Padang City has been done well (74.53%), but must be improved again so that the educational facilities in schools are in good condition and ready to use and can support in the learning process effectively and efficiently.